Pengaruh Penyuluhan menggunakan Media Booklet dan Video Animasi tentang Sayur Buah terhadap Pengetahuan Remaja SMP IT Bina Insani - Indri Silvani; Ratih Kurniasari (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2022)
A balanced intake of nutrients is needed to meet the body's needs. Vegetables and fruits are foods that are rich in vitamins and minerals. The content of nutrients in vegetables and fruit benefits the health, development and growth of a person's body. The population in Karawang Regency is only about 0.96 who consume more than 5 vegetables and fruits per day a week. This is due to lack of knowledge about vegetables and fruits. The purpose of this study was to determine the effect of nutrition counseling using booklets and animated videos on knowledge about vegetables and fruits in junior high school adolescents. This study uses a quasi-experimental design with a pre-test¬ and post-test group design. The subjects of the study were junior high school teenagers aged 12-15 years, totaling 40 people with 2 intervention groups who received education through booklets and animated videos. The results showed that the value of knowledge before and after the intervention with the booklet group before 78.00 increased to 108.50 and for the video animation group before 74.50 it increased to 98.00. The conclusion is that there is an effect of education using booklets and animated videos about vegetables and fruit on the knowledge of junior high school students.